2018
DOI: 10.1017/s1368980018001301
|View full text |Cite
|
Sign up to set email alerts
|

The validity of mid-upper arm circumference as an indicator of low BMI in population screening for undernutrition: a study among adult slum dwellers in eastern India

Abstract: Results supported the validity of the WHO-recommended MUAC cut-offs for adults. There is still a need to establish statistically appropriate MUAC cut-offs to predict undernutrition and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 50 publications
2
27
2
Order By: Relevance
“…These findings suggest that MUAC could be used as a screening tool for adult underweight in a low-resource setting, the same way BMI is currently being used. Other studies have found similar correlations in adult populations [ 2 , 7 , 10 15 ] and with a high correlation across ethnicity and sex. While there is consensus about the usefulness of MUAC, the optimal cutoff to detect underweight is still not determined.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These findings suggest that MUAC could be used as a screening tool for adult underweight in a low-resource setting, the same way BMI is currently being used. Other studies have found similar correlations in adult populations [ 2 , 7 , 10 15 ] and with a high correlation across ethnicity and sex. While there is consensus about the usefulness of MUAC, the optimal cutoff to detect underweight is still not determined.…”
Section: Discussionsupporting
confidence: 71%
“…The cutoff can be described by YI, and with this method, we found that a MUAC of 24.5 cm would be the cutoff best associated with a BMI < 18.5 kg/m 2 . Other studies also using YI found that the MUAC cutoff should be between 21.9–25.1 cm [ 7 , 11 , 13 , 15 , 16 ]. However, we believe the optimal cutoff should not be determined strictly based on an equation, but instead take into account the setting it is to be used in.…”
Section: Discussionmentioning
confidence: 99%
“…We then examined the diagnostic accuracy of MUAC in predicting low BMI, using MUAC cut-offs in increments of 0 GUI-HIV (13) Guinea-Bissau 2007-2009 ART-naïve, HIV-infected patients in Guinea-Bissau 1055 GUI-TBC (27) Guinea-Bissau 2014 Healthy controls and household contacts of TB patients in Guinea-Bissau 769 IND-BKW (28) India 2014-2016 Adult male brick-kiln workers in Murishdabad district, West Bengal, India 501 IND-FSD (9) India 2006 Female slum dwellers in Midnapore Town, West Bengal, India 333 IND-IDU (29) India 2007 Current and former male IDU in Chennai, Tamil Nadu, India 374 IND-MSD (10) India [2003][2004] Male slum dwellers in Kolkata, India 474 IND-ORA (30) India 2007 Oraon men of Gumla District, Jharkhand, India 205 IND-SDW (31) India (33) South Africa 2002 Free-living and institutionalised elderly black South Africans in Cape Town, South Africa…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Various studies have shown a significant correlation between MUAC and BMI, it is known that individuals with low MUAC are likely to have a low BMI. 4,6,[18][19][20][21][22][23] Research conducted by Brito et al 8 on 1373 inpatients at a hospital in Spain, showed that there was a correlation between BMI and MUAC with r = 0.78 (p <0.001). The cut-off point value for detecting malnutrition obtained from this study was 22.5 cm for both men and women.…”
Section: Research About Muac Cut-off Point For Detecting Malnutritionmentioning
confidence: 99%